Comparative Analysis of Hemp Fiber Grown in Year 2010 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Annually increasingly all over the world is observed growing tendency to reduce the production of various products containing non-renewable component and replace them with natural fiber raw materials for textile and non-textile products as well. One of such raw materials is hemp. This paper discusses comparative study results of testing local genotype „Purini“ and commercial available ES registered industrial hemp variety „Bialobrzeskie” (Poland) fibers which were grown in Latvia, year 2010th. Studies have been carried out for small fiber bundles to determine the durability properties of hemp fiber.